A survey on the use of electronic resources in the University of the Philippines College of Science Library and its effect on user's information needs. - Beliran, Joan M. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This study was conducted to identify the particular forms of electronics resources preferred by the users when looking for information; to compile a list on most commonly used electronic resources; to determine the purposes and reasons for using electronic resources; to find out the difficulties and problems encountered while assessing these electronic resources; and to find out how useful are the information they derived using electronic resources.
Three hundred twelve (312) library users were the respondents identified through stratified random sampling. In gathering the necessary information questionnaires were used. Data gathered were organized. tabulated and analyzed using Statistical Software Package for Social Sciences (SPSS). Majority of the respondents were female 175 (56 percent) and most of them are Chemistry majors, 87 (29 percent). Results reveal that 246 (51.2 percent) consulted online resources than CD-ROM 202 (42.8 percent). The paper also presented the most commonly used titles online resources and CD-ROMs, arranged by subject area.
Nature 129 (10.5 percent) is the most popular online resource while Biology 6th ed. 74 (36.6 percent) holds the top spot in Biology, Merck Index 120 (47.8 percent) on Chemistry, Calculus Connection 28 (42.2 percent) on Mathematics, Physics for Scientists and Engineers 24 (41.7 percent) on Physics Molecular Cell Biology 16 (21.6 percent) for MBB and Voyage through the sky 15 (46.9 percent) for Earth Sciences.
The study also revealed that accessibility, 280 (10.7 percent) is the top reason why the users want to access and use electronic resources. Second and third choices are convenience, 272 (10.4 percent) and current information, 261 (10 percent).The difficulties that majority of the respondents encountered are access, because the computers are slow, and lack of computers. With regard to respondents' rating about the usefulness of the information they derived from CD-ROM and online electronic resources, respondents considered CD-ROM "very useful" against Online Electronic Resources.
In order to meet the above-mentioned needs and expectations, the study recommended to provide or allot a budget for acquiring more CD-ROMs and subscription to online resources; problem in allocating a budget for acquiring more CD-ROMs and online resources, UP CSLIB could tie up with other science schools, colleges, universities, organizations and local governments so UP CSLIB could also assess their electronic resources; full support and cooperation from the administration and university especially in upgrading but also in acquiring more state of the art equipment like scanners and printers and possibly a wi-fi in UP CS LIB should further promote the availability of the electronic resources in the library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines College of Science Library; Electronic information resources -- Philippines -- Quezon City